2016
DOI: 10.1111/jopr.12486
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Analysis of Dental Implants in Mandibular Premolar Region: 3D FEM Study

Abstract: The results of this study suggest that dental implants should be covered with crowns as soon as possible, and patients with dental implants should avoid consumption of hot food and beverages without allowing time for the heat to dissipate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 22 publications
3
10
0
Order By: Relevance
“…The former model assumed two materials (zirconia and ceramic) and the latter had no crown. Exposing these FE models to heat loads showed that the ceramic crown exhibits the diffusion of the heat through the deeper implant parts and the surrounding bone [15]. However, their calculated temperature magnitudes, specifically at the BII in delayed-loading implantation type (without crown), were considerably low in comparison with the experiments that applied the same condition [15].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The former model assumed two materials (zirconia and ceramic) and the latter had no crown. Exposing these FE models to heat loads showed that the ceramic crown exhibits the diffusion of the heat through the deeper implant parts and the surrounding bone [15]. However, their calculated temperature magnitudes, specifically at the BII in delayed-loading implantation type (without crown), were considerably low in comparison with the experiments that applied the same condition [15].…”
Section: Introductionmentioning
confidence: 98%
“…Naturally, the cells are recruited to form the bone unless in disorders [14], or severe external conditions e.g. mechanical over-or unloading of the implant [9], extreme heat exposing [15], etc. The heat exposing to the implant is daily and repetitive by beverage of hot liquids or eating hot foods which may adversely affect the osteointegration process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a derivation of the heat equation, the interested reader may consult Appendix A. An additional source term q(t) = m (T-Ts), where m is a constant depending on the type and the geometry of the implant, may be added to take into account the temperature excess due to the thermal loading [25,26].…”
Section: Formulation Of the Physical Problemmentioning
confidence: 99%
“…Thus, the transient heat transfer under thermal load is of vital significance in dentistry, in general, and in practical oro-dental implantology, in particular. In the literature, there already exist some previous works on the subject, where the authors attempted to model and investigate the effects of "thermal load(s)" on the bone-implant interface system [24][25][26][27][28] (see, however, e.g., [29,30] for heat transfer from warm water to foot in a footbath). In this work, our approach is distinct in two main respects: (1) firstly, in the other studies, authors tend to solve the heat equation with a source term that accounts for the temperature excess T-Ts, with (T) being the temperature at a given point and (Ts) being the temperature from the surroundings.…”
Section: Introductionmentioning
confidence: 99%